Determinantes do desempenho escolar no Rio Grande do Sul : uma análise a partir de modelos hierárquicos - Moreira, Kayline da Silva Gomes (2013)
This research aims to investigate the determinants of scholar achievement in the state of Rio Grande do Sul, Brazil, using hierarchical linear models (HLM). The 2007 microdata from Sistema de Avaliação do Rendimento Escolar do Rio Grande do Sul (SAERS) were used to estimate a hierarchical linear model with two levels level student and level school to analyze students performance in Mathematics and Portuguese in Elementary School 5th grade and in the High School 9thgrade. The main result of this study is that students socioeconomics characteristics (represented by goods that the students have and don t have at home) are strong determinants in the scholar achievement, while the school features (represented by the teacher characteristics, school principal characteristics and school infrastructure) contribute very little to explain the performance of the students from Rio Grande do Sul. Not necessarily this result means that school attributes aren t important to explain the performance of the students, but it might mean that school resources have been used inefficiently. The evidences show that it s important to develop strategies to lead public policies in order to expand the role of school in the scholar achievement, so that the pupils can have equal opportunities, especially the neediest.